Ontological support formation for constructive-synthesizing modeling of information systems development processes - Skalozub, Vladislav; Ilman, Valeriy; Shynkarenko, Viktor (Eastern-European Journal of Enterprise Technologies, 2018)
The globalization of information systems (ISs) in the process of continuous operation and modernization creates new problems and reveals specific representations of IS tasks. Such a complex industry IS, requiring appropriate ontological support, is the unified automated system for managing freight traffic of Ukrzaliznytsia (ACS FT UZ-U). To develop the infrastructure information subsystems such as rolling stock and traction staff, traffic management, finance, personnel and a number of others, it is necessary to develop interconnected ontological support. Therefore, methods and means of ontological support of constructive-synthesizing modeling (OCSM) have been developed, designed to support the processes of multistage creation, a long period of operation and the continuous development of the ACS FT UZ-U. The results obtained are distinguished by universalism, as they provide opportunities for representing the evolution of the object (IS) and the content of ontologies in the OCSM. The formation of models and methods of the OCSM has been obtained by expanding relations and mappings as well as by creating new generating structures, complementing classes of signatures with new constructive relations. At the same time, the model of a unified, universal and customizable ontological constructive structure (OCS) has been developed. The OCS takes into account the requirements for representing the processes of expanding the subject area as well as unifying knowledge. For CSM problems, methods and means of modeling the conceptualization processes of developing objects have been created and constructive calculus has been devised for the generating class of mappings along with methods for constructing higher-order ontological objects. For the ontological support of the CSM processes in the context of expanding subject areas, the inference methods in the model of the OCSM constructive structure have been improved and procedures for meaningful, structural and related deducibility have been proposed together with multilevel inference methods. Examples have been given of the implementation of the currently existing procedures for creating new applications of the automated system ACS FT UZ-U using the proposed CSM tools. The examples demonstrate the adequacy of the developed models and means of the OCSM for the implementation of procedures for the development and maintenance of complex railway ACSs